Response Styles and Personality Traits: A Multilevel Analysis. (August 2014) - He, Jia; Bartram, Dave; Inceoglu, Ilke; van de Vijver, Fons J. R.
In two studies, we examined the shared and unique meaning of acquiescent, extreme, midpoint, and socially desirable responding in association with the Occupational Personality Questionnaire (OPQ32), a forced-choice format personality measure designed to be less affected by these response styles, compared with personality inventories with Likert-type scales. Country-level response style indexes were derived from six waves of the International Social Survey Programme and from a meta-analysis of a social desirability scale. In the country-level correlational analysis, the four response styles formed a general response style (GRS) factor which was positively associated with (a) dominance (vs. submission) in interpersonal relationships, (b) competitive (vs. modest and democratic) feelings and emotions, and (c) data rational thinking. In a multilevel analysis, age showed a positive and education a negative effect on the individual-level GRS. Negative effects of country-level socioeconomic development and individualism and positive effects of competitiveness and data rational thinking on the individual-level response style were found. We conclude that country-level response styles are systematically associated with country personality measured by the OPQ32, suggesting that they can be viewed as having substantive meaning (i.e., culturally influenced response amplification vs. moderation). Implications are discussed.